Genome-wide association studies for citric and lactic acids in dairy sheep milk in a New Zealand flock - An Zongqi; Ana C. Marshall; J. M. D. R. Jayawardana; Mike Weeks; Simon M. Loveday; Warren McNabb; Nicolas Lopez-Villalobos (Animal Biotechnology)
The objectives of this study were to estimate genetic parameters for citric acid content (CA) and lactic acid content (LA) in sheep milk and to identify the associated candidate genes in a New Zealand dairy sheep flock. Records from 165 ewes were used. Heritability estimates based on pedigree records for CA and LA were 0.65 and 0.33, respectively. The genetic and phenotypic correlations between CA and LA were strong-moderate and negative. Estimates of genomic heritability for CA and LA were also high (0.85, 0.51) and the genomic correlation between CA and LA was strongly negative (-0.96 ± 0.11). No significant associations were found at the Bonferroni level. However, one intragenic SNP in C1QTNF1 (chromosome 11) was associated with CA, at the chromosomal significance threshold. Another SNP associated with CA was intergenic (chromosome 15). For LA, the most notable SNP was intragenic in CYTH1 (chromosome 11), the other two SNPs were intragenic in MGAT5B and TIMP2 (chromosome 11), and four SNPs were intergenic (chromosomes 1 and 24). The functions of candidate genes indicate that CA and LA could potentially be used as biomarkers for energy balance and clinical mastitis. Further research is recommended to validate the present results.